Hollow Section Fibers Characterization for Seats Covers Fabric Application - Brunella, Valentina; Albini, Giulia; Lambertini, Vito Guido; Placenza, Bartolomeo (Frontiers in Materials, 2020)
This research is focused on hollow polyethylene terephthalate (PET) fibres and fabrics. The aim of hollow section fibres application is a textile contribution to weight reduction of the whole vehicle. CO2 emissions consequences and awareness of companies to environmental issues are driving studies on the direction of vehicle weight reduction, according to recent European regulations. For this purpose, fabrics composed of hollow fibres have been produced and characterized. In order to be applied as seats covers for the automotive sector, they have been compared to current production woven fabrics. Tensile, tear strength tests and aesthetic and structural abrasion have been carried out. The performance of hollow fibres PET fabrics is slightly lower than full section fabrics, but completely acceptable according to automotive requirements. Its specific application can be evaluated.